(untitled) - Abdul Aziz; Javed Ahmed Memon; Ashfaque Ali Banbhan; Sadia Anwar; Azeem akhtar bhatti (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Globalization has witnessed a massive upheaval and upswing in recent times which has resulted in building outsourcing as one of the most preferred and popular choice of policy and plan of action for organizations especially in the manufacturing industry in order to streamline operations and deliver exceptional customer experience. It is a good topic to add value to the existing domain of facts by examining the relationship between third party outsourcing and profitability of a company in manufacturing sector. The manufacturing plants of an organization can be on site or outside the vicinity and subcontracted to another company in a totally different locality. To find out the impact of outsourcing we selected garment and shoe industry located in Karachi. We took logistics and manufacturing for our study. The two departments of twenty companies operating in Karachi were selected. Our findings say that outsourcing of logistics and manufacturing have given positive impact on businesses of these selected companies.